HOZIRGI O‘ZBEK VA QORAQALPOQ ADABIY TILLARIDA KOMPONENT TARKIBI TURLI XIL BO‘LGAN SINONIM FRAZEMALAR - Xaytbayev, O. (SCIENCE and SOCIETY, 2024)
The article provides theoretical and practical examples of synonymous phrases with different components in modern Uzbek and Karakalpak literary languages.
Keywords: phrase; component; seme; synonymous phrase; semantic component